Compound fire‐drought regimes promote ecosystem transitions in Mediterranean ecosystems. (19th December 2018) - Batllori, Enric; De Cáceres, Miquel; Brotons, Lluís; Ackerly, David D.; Moritz, Max A.; Lloret, Francisco
Abstract: Understanding ecosystem responses to compound disturbance regimes and the influence of specific sequences of events in determining ecosystem shifts remains a challenge. We use a modelling framework for Mediterranean‐type ecosystems to assess the effects of fire–drought interactions on long‐term vegetation dynamics and to identify disturbance‐driven changes in trait composition (tree seeder vs. tree resprouter prevalence) and ecosystem state (forest vs. non‐forest). Changes in tree seeder and the tree resprouter dominance show nonlinear, threshold‐type trends over gradients of increasing compound disturbance frequency. Vegetation composition thresholds mostly occur in a narrow range of the compound fire–drought disturbance space. Additionally, trait compositional switches and the likelihood of sudden changes in ecosystem state are promoted by fire‐drought interactions. Distinct sequences of disturbance events cause vegetation transitions, disrupting ecosystem resilience, even under moderate recurrence of individual disturbances. An extreme drought year followed by one or two large fire events promotes shifts from resprouter‐ to seeder dominance. Contrastingly, a large crown fire followed by an extreme drought promotes changes from seeder to resprouter dominance. This disturbance sequence is also a mechanism strong enough to trigger sudden shifts in ecosystem state (from forest to non‐forest). Synthesis . Thresholds of change in vegetation composition occur over a narrow range of the modelled gradients of compound fire‐drought recurrence, and the loss of ecosystem resilience is contingent on particular sequences of disturbance events. Overall, our findings highlight that disturbance interactions define the relative location of tipping points in ecosystem state, and that effects and feedbacks of compound disturbance regimes increase the long‐term likelihood of sudden ecosystem shifts and, therefore, uncertainty in predicting vegetation state. Abstract : Thresholds of change in vegetation composition occur over a narrow range of the modelled gradients of compound fire‐drought recurrence, and the loss of ecosystem resilience is contingent on particular sequences of disturbance events. Overall, our findings highlight that disturbance interactions define the relative location of tipping points in ecosystem state, and that effects and feedbacks of compound disturbance regimes increase the long‐term likelihood of sudden ecosystem shifts and, therefore, uncertainty in predicting vegetation state.